2009
DOI: 10.1002/smj.808
|View full text |Cite
|
Sign up to set email alerts
|

The use of an interim CEO during succession episodes and firm performance

Abstract: Our study investigates an unexplored succession process—interim CEO successions. We define an interim CEO succession as a case where the title of chief executive officer is vacated by the incumbent and the board of directors has not announced a permanent successor, but instead designates a particular individual as ‘interim CEO,’ or ‘acting CEO,’ or ‘CEO until a permanent successor is named.’ Theory predicts that interim CEO successions will lead to the type of disruption that can harm firm performance, even af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
194
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(200 citation statements)
references
References 71 publications
3
194
0
1
Order By: Relevance
“…However, this research domain is rife with unanswered questions regarding the impact of utilizing interim versus permanent leaders. In particular, while work in this area has focused on the performance implications of selecting an interim as compared to a permanent replacement (e.g., Ballinger and Marcel 2010) as well as the factors that may lead to the decision to select an interim leader in the first place (e.g., Mooney et al 2014), little is known about how an interim leader needs to manage once they are selected and whether interim vs. permanent leaders should enact leadership functions differently. We expect that interim vs. permanent status is a boundary condition on the proposed interactive relationship between action phase functional leadership and the team's strategic core human capital.…”
Section: Interim Vs Bpermanent^leader Transitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this research domain is rife with unanswered questions regarding the impact of utilizing interim versus permanent leaders. In particular, while work in this area has focused on the performance implications of selecting an interim as compared to a permanent replacement (e.g., Ballinger and Marcel 2010) as well as the factors that may lead to the decision to select an interim leader in the first place (e.g., Mooney et al 2014), little is known about how an interim leader needs to manage once they are selected and whether interim vs. permanent leaders should enact leadership functions differently. We expect that interim vs. permanent status is a boundary condition on the proposed interactive relationship between action phase functional leadership and the team's strategic core human capital.…”
Section: Interim Vs Bpermanent^leader Transitionsmentioning
confidence: 99%
“…In addition, by actively monitoring team activities, diagnosing problems, and leveraging the team's strategic core human capital resources to satisfy needs or resolve problems, interim leaders may be able to minimize the disruption from the transition and help the team to maintain focus on its goals. Likewise, taking such an active leadership approach may enable the interim leader to build credibility and overcome any preconceived notions that he/she is just a placeholder and that the team will operate in the status quo until a permanent replacement is named (e.g., Ballinger and Marcel 2010). Similarly, prior research has demonstrated that in order for leaders to be successful, they need to have the trust of their team members (Dirks 2000).…”
Section: Interim Vs Bpermanent^leader Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. Interim CEOs are used during times of uncertainty (e.g., Mooney, Semadeni, & Kesner, in press) and are associated with negative performance (e.g., Ballinger & Marcel, 2010). Ascension Process 4.…”
Section: Figurementioning
confidence: 99%
“…In fact, the leader is able to follow an active strategy, enabling him to expand his discretionary space through neutralizing certain constraints bearing on his management. In this context, many studies have pointed to the existence of deviation strategies adopted by managers in order to eschew control mechanisms or to overcome them [47], [62] [7], and [81] explained that the manager who seeks to entrench himself uses the firm's resources in order to invest in specific investment projects, which make its replacement costly for shareholders. Other authors including [62], [27], and [2] postulated that diversification investments can be analyzed as means for increasing power, managers' entrenchment and reducing other business partners.…”
Section: Entrenchment and Manager's Active Behaviormentioning
confidence: 99%